Some Thiazolopyrimidine Derivatives: Synthesis, DFT, Cytotoxicity, and Pharmacokinetics Modeling Study - Alzahrani, Abdullah Y. A.; El-Helw, Eman A. E.; Ramadan, Sayed K. (Synlett, 2024)
A pyrimidinethione candidate carrying pyrazole and thiophene scaffolds was produced by a Biginelli cyclocondensation reaction of a pyrazolecarbaldehyde with pentan-2,4-dione and thiourea. To create some heteroannulated thiazolopyrimidines, the pyrimidinethione was subjected to cyclocondensation reactions with ethyl chloroacetate, 1,2-dibromoethane, chloroacetonitrile, and oxalyl chloride. A DFT simulation was performed for a frontier-orbital analysis to determine the molecular geometry. Among the products, 6-acetyl-7-methyl-5-[1-phenyl-3-(2-thienyl)-1H-pyrazol-4-yl]-5H-[1,3]thiazolo[3,2-a]pyrimidine-2,3-dione displayed the highest softness and the lowest energy gap in the DFT calculations. Moreover, it had the highest electrophilicity index, suggesting possible biological impacts. The compounds obtained were evaluated against cell lines of breast adenocarcinoma (MCF7) and hepatocellular carcinoma (HepG2) as antiproliferative agents. A simulation of the molecular docking of our compounds with the epidermal growth factor receptor demonstrated the rationality of our design and identified the binding mode. A model pharmacokinetics analysis showed that the products have the expected and desirable drug-like and bioavailability properties.
Keywords: cytotoxicity; density functional theory; pharmacokinetic modelling; pyrimidinethiones; thiazolopyrimidines